PÄDAGOGISCHE INNOVATIONEN IN DER VORBERUFLICHEN BILDUNG. BERICHT ÜBER EINE VON DEN INITIATIVEN DER „GESELLSCHAFT FÜR ARBEIT, TECHNIK UND WIRTSCHAFT IM UNTERRICHT” (GATWU) - Oberliesen, Rolf (Wydawnictwo Naukowe UAM w Poznaniu, 1991)
Oberliesen Rolf, Pädagogische Innovationen in der vorberuflichen Bildung. Bericht über eine von den Initiativen der „Gesellschaft für Arbeit, Technik und Wirtschaft im Unterricht” (GATWU) (Pedagogical innovations in the pre-professional education. Information on the initiatives of the „Gesellschaft für Arbeit, Technik und Wirtschaft im Unterricht” (GATWU), „Neodidagmata” XX, Poznań 1991, Adam Mickiewicz University Press, pp. 147-149. ISBN 83-232-0302-4. ISSN 0077-653X. Received: Dezember 1990. Changes in the professional world which result from application of modern information and communication technologies in production, administration, services, lead to fundamental transformations in educational system. The technical and economic education becomes therefore an integral component of general education. Perspectives of international economic co-operation depend also on the constant exchange of information and co-operation in the field of education between the countries of Western and Eastern Europe. As an example of initiatives in this field the author presents the report from the international symposium devoted to the problems of pre-professional education which took place in the autumn of 1989 in Sonnenberg in the Federal Republic of Germany. The article also shows the field of pedagogical interests and activities of the "Gesellschaft für Arbeit, Technik und Wirtschaft im Unterricht” (GATWU).
Keywords: Technologie komunikacyjne; Communication technologies; Technologia informacyjna; Information technology; Edukacja informatyczna; Computer science; Szkoła niemiecka; German school